Breeding range expansion and population distribution shifts of Magellanic Penguins in northern Patagonia, Argentina - Garcia Borboroglu, Jorge Pablo (2019)
Understanding changes in seabird distribution and abundance is fundamental to effectively direct conservation and management strategies. Magellanic penguins (Spheniscus magellanicus) have 66 breeding colonies distributed along 4000 km of coastline in Patagonia, Argentina, with a global population of 1.2-1.6 million pairs. We updated the distribution pattern and estimated colony size and trends at the stronghold of the global population, located along the northernmost Atlantic breeding range. In this 1,000 km sector, we censused 28 colonies that total 628,000 pairs, representing 42% of the extant colonies and 57% of the global population. Colony sizes were highly variable, from 31 breeding pairs in Isla Vernaci Sudoeste (45°S) to 199,140 in Estancia San Lorenzo (42°S). Mean and maximum density (active nests/100m2) were variable among colonies, but the highest values were found in northern Chubut (Estancia San Lorenzo, dmax = 83) and the lowest in golfo San Jorge, southern Chubut (Isla Tovita, dmax = 7). Colony growth rates were variable, but virtually all colonies located in the northernmost area (Rio Negro and northern Chubut) continued showing consistently high rates, while in central and southern Chubut colonies declined or remained relatively stable. Estancia San Lorenzo became the largest colony known for the species, exceeding Punta Tombo (42°) by approximately 60,000 pairs. Recently, new colonies expanded the species breeding distribution range; Punta Pozos (41°S) in 2014 and Bahía San Antonio (40°S) in 2018.The northward redistribution of the metapopulation is generating new conservation and management challenges, particularly related to tourism development.